Symptom association probability does not reliably distinguish functional heartburn from reflux hypersensitivity. Issue 7 (26th January 2018) - Choksi, Y.; Slaughter, J. C.; Sharda, R.; Higginbotham, T.; Lal, P.; Vaezi, M. F.
Summary: Background: Symptom association probability (SAP) is thought to distinguish reflux hypersensitivity from functional disorders. A diagnosis of hypersensitive oesophagus (SAP‐positive) indicates that gastro‐oesophageal reflux disease (GERD) is the cause of continued symptoms. Aim: To conduct an analysis of pH and symptom criteria that lead to a diagnosis of SAP‐positivity Methods: We calculated SAP for 205 patients with GERD symptoms refractory to proton pump inhibitor (PPI) therapy who underwent endoscopy with wireless pH monitoring from 2007 to 2014. Patients were divided into three groups: pH‐negative with no oesophagitis (n = 45), pH‐positive with no oesophagitis (n = 130), and patients with oesophagitis (n = 30). We constructed a 2 × 2 table of symptom and reflux event association and quantified the number of 2‐minute intervals for each of the 2 × 2 variables that distinguished SAP‐positive from SAP‐negative. In a separate cohort of 58 patients who had undergone anti‐reflux surgery, we evaluated the effects of pre‐surgery SAP. Results: The difference in symptom association parameters that led to a diagnosis of an SAP‐positive was small (2.98% in oesophagitis‐positive; 1.56% in oesophagitis‐negative/pH‐positive; 0.48% in oesophagitis‐negative/pH‐negative). In the pH‐negative/oesophagitis‐negative group, a difference of 0.48% led to a diagnosis of hypersensitivity. There was significant variability in SAP values between day 1 and day 2 of pH testing in all groups, with the greatest in the oesophagitis‐positive group, despite objective evidence for reflux (27% in oesophagitis‐positive, 19% pH‐positive/oesophagitis‐negative, and 7% in pH‐negative/oesophagitis‐negative). Pre‐surgery SAP was not associated with response to anti‐reflux surgery. Conclusion: In PPI‐refractory GERD, SAP cannot accurately distinguish reflux hypersensitivity from functional oesophageal symptoms. Abstract : Linked Content This article is linked to Triggs and Kahrilas paper. To view this article visithttps://doi.org/10.1111/apt.14583 .